Water permeation across artificial I-quartet membrane channels: from structure to disorder. (5th July 2018) - Murail, Samuel; Vasiliu, Tudor; Neamtu, Andrei; Barboiu, Mihail; Sterpone, Fabio; Baaden, Marc
Abstract : Investigation of water dynamics during permeation events through I-quartet membrane channels in ordered and disordered systems. Abstract : Artificial water channels (AWCs) have been designed for water transport across membranes with the aim to mimic the high water permeability observed for biological systems such as aquaporins (∼10 8 –10 9 water molecules per s per channel), as well as their selectivity to reject ion permeation at the same time. Recent works on designed self-assembling alkylureido-ethylimidazole compounds forming imidazole-quartet channels (I-quartets), have shown both high water permeability and total ionic-rejection. I-quartets are thus promising candidates for further development of AWCs. However, the molecular mechanism of water permeation as well as I-quartet organization and stability in a membrane environment need to be fully understood to guide their optimal design. Here, we use a wide range of all-atom molecular dynamics (MD) simulations and their analysis to understand the structure/activity relationships of the I-quartet channels. Four different types with varying alkyl chain length or chirality have been studied in a complex fully hydrated lipid bilayer environment at both microsecond and nanosecond scale. Microsecond simulations show two distinct behaviors; (i) two out of four systems maintain chiral dipolar oriented water wires, but also undergo a strong reorganization of the crystal shape, (ii) the two other I-quartet channels completely lose the initial organization, nonetheless keeping a water transport activity. Short MD simulations with higher time resolution were conducted to characterize the dynamic properties of water molecules in these model channels and provided a detailed hypothesis on the molecular mechanism of water permeation. The ordered confined water was characterized with quantitative measures of hydrogen-bond life-time and single particle dynamics, showing variability among I-quartet channels. We will further discuss the underlying assumptions, currently based on self-aggregation simulations and crystal patches embedded in lipid bilayer simulations and attempt to describe possible alternative approaches to computationally capture the water permeation mechanism and the self-assembly process of these AWCs.